Reliability evaluation for cantilevered retaining walls considering uncertainty of mainshock-aftershock sequences. Issue 163 (December 2022) - Zhou, Yang; Jing, Mingyuan; Pang, Rui; Xu, Bin
Abstract: A method for the probabilistic analysis and reliability evaluation of retaining walls is presented in this paper. This paper examines the stochastic dynamic response of the rigid cantilever retaining wall subjected to mainshock-aftershock sequences. A variable generation strategy for minimizing the lowest generalized F-discrepancy is used to facilitate the simulation of stochastic seismic sequences. The correlation between the main shock and the aftershock is established through a copula function. The direct probability integral method (DPIM) is used to estimate the reliability of the retaining wall when the wall is subjected to stochastic seismic sequences. The results show that the dynamic reliability of different physical quantities at different safety thresholds can be obtained by the above methods without assuming the probability distribution of the response. This study also demonstrates that aftershocks can degrade the structural reliability to varying degrees, with the degradation intensifying in proportion to the increase in design requirements. Highlights: A mainshock-aftershock sequences model consistent with optimal point selection strategy is proposed. The dependence between main shock and aftershock is established. Established an efficient method for stochastic dynamic analysis of retaining walls subjected to seismic sequences. The influence of aftershocks on the reliability of the retaining wall is discussed based on DPIM.